Stability of Rocket Flight during Burning - Srivastava, T. N.; Singh, Manak (Defence Science Journal, 2014)
Stability of the rocket motion during burning is discussed taking into consideration gravity, aerodynamic forces and torques. Conditions for stabilizing the rocket motion are investigated. Analysis for initial and final phases of burning is given separately. Stability regions of the projected motions on two dimensional co-ordinate planes are obtained and thereby stability region of the actual motion is derived. Stability diagrams illustrate statically and dynamically stable and unstable regions.